Adverse events among people on delamanid for rifampicin-resistant tuberculosis in a high HIV prevalence setting - Hughes, J; Reuter, A; Chabalala, B; Isaakidis, P; Cox, H; Mohr, E (The international journal of tuberculosis and lung disease, 2019)
Patients with rifampicin-resistant tuberculosis (RR-TB) in the township of Khayelitsha, South Africa, were offered delamanid (DLM) within a decentralised RR-TB treatment programme. To describe adverse events (AEs) among HIV-positive and negative people receiving DLM for RR-TB in a programmatic setting. Patients were followed up monthly for blood, electrocardiography and clinical monitoring and AEs were assessed for severity grade, seriousness and relationship to DLM. Fifty-eight patients (55% male; median age 35 years, interquartile range [IQR] 28-42) started DLM; 46 (79%) were HIV-positive, median CD4 count 173 cells/mm³ (IQR 70-294). Fifty (86%) patients experienced ≥1 new or worsening AE after starting DLM, most commonly vomiting, QTcB >450 ms and/or myalgia. Serious and/or severe AEs were experienced by 22 (38%) patients; three HIV-positive patients died (not related to DLM). HIV status was not significantly associated with number ( 0.089) or severity/seriousness ( 0.11) of AEs during exposure to DLM. Two (3%) patients had DLM withdrawn due to AEs. AEs during RR-TB treatment, both before and during DLM exposure, were common, with relatively few serious/severe AEs considered related to DLM and no significant association with HIV status. Clinical and electrocardiography monitoring should be prioritised in the first two months after starting DLM.